Recommendations for Diagnosis and Management of Autoimmune Pancreatitis in Childhood: Consensus From INSPPIRE. Issue 2 (August 2018) - Scheers, Isabelle; Palermo, Joseph J.; Freedman, Steven; Wilschanski, Michael; Shah, Uzma; Abu-El-Haija, Maisam; Barth, Bradley; Fishman, Douglas S.; Gariepy, Cheryl; Giefer, Matthew J.; Heyman, Melvin B.; Himes, Ryan W.; et al.
ABSTRACT: Objectives: Autoimmune pancreatitis (AIP) represents a complex immune-mediated pancreas disorder. Pediatric AIP (P-AIP) is rare. We have recently summarized the characteristic features of P-AIP. We now aim to develop recommendation statements to standardize the diagnostic and therapeutic approach to P-AIP and facilitate future research in the field. Methods: A panel of pediatric gastroenterologists participating in theIn ternationalS tudy Group ofP ediatricP ancreatitis:I n search for a cuRE was formed to discuss and then vote on 15 recommendation statements. A consensus of at least 80% was obtained following 3 voting rounds and revision of the statements. Results: We have now generated 15 statements to help standardize the approach to diagnosis and management of P-AIP. Conclusions: The first P-AIP recommendation statements developed by theIn ternationalS tudy Group ofP ediatricP ancreatitis:I n search for a cuRE group are intended to bring standardization to the diagnosis and treatment of this rare childhood disorder. These statements may help guide a uniform approach to patient care and facilitate future research studies.